STRATEGI COMMUNITY DEVELOPMENT PT. RIAU ANDALAN PULP AND PAPER (RAPP) DALAM MELAKSANAKAN PROGRAM SMALL MEDIUM ENTREPRENUER’S (SME’s) - Putra, Fauzi Lesmana; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research is motivated by the emergence of one of the programs that harness the power of community empowerment as a partner building company that had the talent and Small and Medium Enterprises (SMEs) in Pelalawan. The program is called program Entreprenuer's Small Medium (SME's), one of the Community Development program of PT. RAPP-related assistance in micro-scale enterprises, small to medium-sized. Program Entreprenuer's Small Medium (SME's) is a partnership mutually beneficial business between small businesses and large businesses along with the coaching and development by large employers, mutual need, benefit and strengthen. Until now, SME's program is still running and growing rapidly. The method used in this research is descriptive qualitative. The data in this study is divided into two primary data, in the form of interviews and observations. And secondary data, in the form of documentation, archives, as well as a general overview of the location of research in getting from PT. RAPP. Data collection uses interviews, observation and documentation. In this study, there were 5 people whom the authors took as informants to provide the data that the authors needed. Data analysis techniques in this study are using the Milles and Huberman models and data validity checking techniques that extend participation and triangulation.The results showed that the strategies implemented by PT. RAPP has been quite successful because it has a big impact for the community, especially community development partners of the company. However, in the application of innovation strategy still needs development of creative ideas in order to create a superior program and is better known by the public. Factors supporting the implementation of the program Entreprenuer's Small Medium (SME's): Management, Access Capital and Marketing, Cooperation with the Government, as well as family support. While the inhibiting factors in the implementation of the program Entreprenuer's Small Medium (SME's), namely: Human Resources (HR) and the number of SMEs who do not have a legal operating license.